The Impact of the Definitions of Clinical Phases on the Profiles of Grey-Zone Patients with Chronic Hepatitis B Virus Infection - Xiaoqian Xu; Hao Wang; Shan Shan; Yameng Sun; Xiaoyuan Xu; Hong You; Jidong Jia; Hui Zhuang; Yuanyuan Kong; on behalf of the China Registry of Hepatitis B (CR-HepB) Group (Viruses, 2023)
We aim to investigate the impact of different clinical phases’ definitions of chronic hepatitis B (CHB) infection on the profiles of grey zone, based on HBV guidelines set by the Chinese Society of Hepatology and Chinese Society of Infectious Diseases (CSH/CSID, 2022 version) and guidelines set by the American Association for the Study of Liver Diseases (AASLD, 2018 version). We retrospectively examined untreated CHB patients enrolled in the China Registry of Hepatitis B database. Patients’ clinical phases were determined as per CSH/CSID and AASLD. Liver fibrosis was estimated by FIB-4 and/or APRI. Among 3462 CHB patients, 56.9% and 41.7% fell into the grey zone based on AASLD and CSH/CSID. Compared with grey zone patients as per AASLD, those under CSH/CSID guidelines showed lower levels of median ALT (26.0 vs. 37.0 U/L, p < 0.001), AST (25.0 vs. 29.4 U/L, p < 0.001) and APRI (0.3 vs. 0.4, p < 0.001), and lower rates of advanced fibrosis estimated by APRI (7.9% vs. 11.4% p = 0.001), but comparable rates by FIB-4 (13.0% vs. 14.1%, p = 0.389). With the stepwise lowering of ALT upper limits of normal (ULN) values from 50/40 U/L for males/females to 40/40 U/L, 35/25 U/L and 30/19 U/L, the proportions of grey zone patients as per CSH/CSID declined from 46.7% to 41.7%, 34.3% and 28.8%, respectively, whereas they remained stable (55.7%, 56.2%, 56.9% and 57.0%) as per AASLD. Compared with the AASLD guidelines, CSH/CSID guidelines leave fewer and less severe patients in the grey zone. Lowering ALT ULN values reduces the number of grey zone patients as per CSH/CSID, but not under AASLD guidelines.